Subnational Taxes in Developing Countries: The Way Forward - BAHL, ROY; BIRD, RICHARD (Public budgeting & finance, 2008)
Both theory and experience in a variety of circumstances around the world suggest strongly that if fiscal decentralization is to produce sustainable net benefits in developing countries, subnational governments require much more real taxing power than they now have. Students of public finance have studied the subject, and practitioners in developing countries have installed many different versions of subnational government tax. In most developing countries there are potentially sound and productive taxes that subnational governments could use: personal income tax surcharges, property taxes, taxes on the use of motor vehicles, payroll taxes, and even subnational value‐added taxes and local “business value” taxes may all be viable options in particular countries. Still, there is no general consensus about what works and what does not. In this review paper, we try and pull together enough evidence to suggest the way forward. We also develop the argument that given political realities one cannot usually decentralize significant revenues to subnational governments without having in place an intergovernmental transfer system to offset at least some of the disequalizing effects that would otherwise occur. Nor does it make sense to think of decentralizing exactly the same package of tax choices to all subnational governments regardless of their scale and scope of operations.